Identification of the nature of management control's contribution to performance piloting in Moroccan companies under digital transformations - Alami, Mohamed; Laouane, Adil (Eastern-European Journal of Enterprise Technologies, 2026)
This study examines the contribution of management control to performance piloting in Moroccan companies in a digital context, focusing on how differences in digital maturity reconfigure this contribution. The problem addressed concerns regarding how the type of digital technologies adopted and its degree of integration explain which conditions they maintain, reinforce, or marginalize the contribution of management control in performance piloting. The study adopted qualitative research based on semi-structured interviews conducted with 23 managers from 10 companies. The findings show that digitalization significantly affects the contribution of management control. In firms using fully integrated ERP (enterprise resource planning) systems, a strong association (r ≥ 0.7) appears between tool automation, performance measurement, and the declining role of management control. In contrast, partially integrated ERP is correlated (r ≥ 0.65) with maintaining the traditional role of management control. However, adopting specific or standardized systems are associated with the gradual marginalization or possible suppression of the management control function. This study identifies distinct configurations of management control contributions depending on the nature of the IT adopted and the level of ERP integration. The analysis shows that attitudes toward digital technologies and decision-making effectiveness shape this contribution by influencing the level of effective technology use. The results also indicate that integration automates most management control tasks related to performance piloting, thereby limiting the contribution of the management control function. These results can guide responsible in redefining the objectives and tasks of management control, depending on the level of digitalization they have achieved